Enantioselective quantitation of the ecstasy compound ( R)- and ( S)- N-ethyl-3,4-methylenedioxyamphetamine and its major metabolites in human plasma and urine - Buechler, Jochen; Schwab, Matthias; Mikus, Gerd; Fischer, Beate; Hermle, Leo; Marx, Claudia; Grön, Georg; Spitzer, Manfred; Kovar, Karl-Artur (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2003)
An enantioselective HPLC method has been developed and validated for the stereospecific analysis of N-ethyl-3,4-methylenedioxyamphetamine (MDE) and its major metabolites N-ethyl-4-hydroxy-3-methoxyamphetamine (HME) and 3,4-methylenedioxyamphetamine (MDA). These compounds have been analyzed both from human plasma and urine after administration of 70 mg pure MDE-hydrochloride enantiomers to four subjects. The samples were prepared by hydrolysis of the o-glucuronate and sulfate conjugates using β-glucuronidase/arylsulfatase and solid-phase extraction with a cation-exchange phase. A chiral stationary protein phase (chiral-CBH) was used for the stereoselective determination of MDE, HME and MDA in a single HPLC run using sodium dihydrogenphosphate, ethylendiaminetetraacetic acid disodium salt and isopropanol as the mobile phase (pH 6.44) and fluorimetric detection ( λ ex 286 nm, λ em 322 nm). Moreover, a suitable internal standard ( N-ethyl-3,4-methylenedioxybenzylamine) was synthesized and qualified for quantitation purposes. The method showed high recovery rates (>95%) and limits of quantitation for MDE and MDA of 5 ng/ml and for HME of 10 ng/ml. The RSDs for all working ranges of MDE, MDA and HME in plasma and urine, respectively, were less than 1.5%. After validation of the analytical methods in plasma and urine samples pharmacokinetic parameters were calculated. The plasma concentrations of ( R)-MDE exceeded those of the S-enantiomer (ratio R: S of the area under the curve, 3.1) and the plasma half time of ( R)-MDE was longer than that of ( S)-MDE (7.9 vs. 4.0 h). In contrast, the stereochemical disposition of the MDE metabolites HME and MDA was reversed. Concentrations of the ( S)-metabolites in plasma of volunteers were much higher than those of the ( R)-enantiomers.